A fé cruza as montanhas: a festa da "Virgen Del Carmen" nas vozes dos imigrantes chilenos na cidade de São Paulo - Yokoyama, Mónica Patricia Diaz Rojas (2015)
São Paulo, city and state, went through an intense and profuse immigration process result of which, it produces a full range of cultural richness and variety. The immigration wave from the late nineteenth century became significantly Latin from the second half of the twentieth century, when thousands of Spanish-speaking immigrants arrived here looking for new and fresh opportunities, coming from multiple dictatorships that ravaged the continent, particularly in the Southern Cone. The Chilean immigrants were among the first to reach this metropolis, bringing a diverse and copious Chilean cultural background. Regarding to other immigrants who settled here with posterity, it was obviously clear the arrival of the marks, the evidence of its presence in this multiple cultured São Paulo. Religiosity as manifestations of culture, memory and identity is one of the last migratory habits that one group leaves, given, to be ingrained customs and practices inherent in its conformation. The manifestations of these religious practices suffer reinterpretation, linguistic and performing adjustments, however, devotion remains constant and is denoted and cyclically in the environment where it operates. This dissertation aims at studying the continuity and silences of these Chilean immigrants to São Paulo between 1973 and 2013 as much as their cultural and gastronomic expressions summarized in "Fiesta de la Virgen del Carmen" compendium of devotion and identity aspects in its redefinition